DIVIDED SUBJECTIVITIES: WOMEN’S MAJELIS TAKLIM RESPONSE TO THE ISLAMIST PREACHERS IN SURAKARTA DIVIDED SUBJECTIVITIES: WOMEN’S MAJELIS TAKLIM RESPONSE TO THE ISLAMIST PREACHERS IN SURAKARTA - Okta Nurul Hidayati (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This paper examines question of the influence of Islamist preachers to the ideology and piety activities of the women majelis taklim in Surakarta. It ask about the involvement of the Islamist preachers in reproducing and spreading the ideas of Islamism in the women majelis taklim (religious gatherings mostly attended by women). This article concerned with Muslim women’s subjectivities and response to the Islamist movement in Surakarta. Using qualitative research methods, this article collects data by interview the congregations and the administrators of three majelis taklim-Al Husna, Humaira, and Da'wah Squad. This paper show that there are divided subjectivities in women’s responses to the Islamist preacher. At the group (majelis) level, especially at Al Husna, there is a potential for expansion of the Islamist movement which was proven by their support for Islamist propagations delivered by the preacher. Da'wah Squad and Humaira show a different response in limiting Islamism by creating their own assemblies curriculum, which is more inclusive. However, at the individual level, some administrators and congregations of the three Majelis have shown their potential for narrowing the Islamist movement with different variations. This research contributes in presenting the emergence of new Muslim women's actors as part of the women's piety movement within the context of emerging Islamism in Surakarta.